Enhancement of Electrical Conductivity of Polyaniline Synthesized by using Carbon Nanofiber - Rahman, M. M.; Sarker, D. R.; Rahman, M. M.; Faruk, M. O. (Journal of Scientific Research, 2021)
Carbon nanofiber (CNF) is a very useful additive for improving the performance of polymer matrix composites, but the performance has sometimes been interrupted by limits appear within composite processing. Recently, CNF based polymer composites are intensely considered as promising materials in many application fields, such as electrical devices, electrode materials for batteries, supercapacitors, sensors, etc. Among these, the electrical conductivity is always the first priority need to be considered. Polyaniline (PANI) and PANI-CNF composites are synthesized by chemical oxidative polymerization of aniline monomers in acidic media. The electrical conductivity of PANI-CNF composites were found varies with the degree of amount of CNF under the effect of multiple factors such as the concentration of aniline monomer, reaction media, oxidant, reaction temperature, reaction time, etc. The maximum electrical conductivity was found 3.7131 S/cm of the PANI-CNF composite coming from the polymerization of aniline with 0.05 g CNF. The results of the synthesis also demonstrated that CNF can be an effective material to prepare electrically conducting polymer composites with ordered nanostructures.